Absolute Not Relative Interocular Luminance Modulates Sensory Eye Dominance Plasticity in Adults. (26th December 2017) - Yao, Zhimo; He, Zhifen; Wang, Yonghua; Lu, Fan; Qu, Jia; Zhou, Jiawei; Hess, Robert F.
Highlights: Monocular luminance deprivation for a period of 2.5 h boosts the patched eye's contribution in binocular combination. This effect doesn't depend on the relative interocular luminance imbalance per se. This effect doesn't depend on the low luminance of the deprived eye per se. This effect depends on the absolute luminance in each eye. Monocular luminance-dependent changes in contrast gain can result in neuroplastic changes in ocular dominance. Abstract: If one eye is patched for a period of 2.5 h in human adults, transient changes in sensory eye dominance result with the previously patched eye's contribution being strengthened. Similar changes result from opaque and translucent occlusion suggesting that it is the deprivation of contrast not luminance information that drives these transient shift of sensory eye dominance. However, this does not rule out the possibility that luminance deprivation per se cannot produce changes in sensory eye dominance, indeed based on what we know of the physiology, where the contrast gain of visual neurons is luminance dependent, one would expect it should. We show that if the mean luminance of one eye is reduced 1000-fold for a period of 2.5 h, there are subsequent changes in sensory eye dominance. With further control experiments we show that this deprivation effect critically depends on the absolute luminance of each eye rather than the relative interocular luminance imbalance. These results indicate that changes in contrast gain at an early, monocular stage of the pathway can result in the transient shift of sensory eye dominance.